PENGUATAN KAPASITAS PENGELOLAAN PELANGGAN MELALUI PELATIHAN CUSTOMER RELATIONSHIP MANAGEMENT BAGI UMKM DESA PANDAU JAYA - Hamanda Hadi Saputra; Tessa Shasrini; Deswarta Deswarta; Hidayat Hidayat; Imam Taqiyuddin Al Fikri; Fyzariadi Fyzariadi (Komunitas Manajemen Kompetitif, 2026)
Micro, small, and medium enterprises in Pandau Jaya Village, Siak Hulu District, Kampar Regency, still face limitations in market reach, customer data recording, and focused marketing communication. This community engagement program aimed to strengthen customer management capacity through practical Customer Relationship Management training aligned with the MSME context. The partner was the MSME group of Pandau Jaya Village, administratively consisting of 30 members. The activity was conducted on 5 December 2025 using a participatory approach through coordination, material delivery, discussion, case studies, customer record practice, and reflection. Evaluation was descriptive and based on participant engagement, discussion responses, and participants ability to identify customer management needs. The results show that participants began to understand CRM as a business strategy rather than merely an application. Participants were also able to identify potential customers, design more focused communication, and use digital media as a customer relationship channel. The program recommends the 4C CRM model: customer record, customer classification, communication plan, and continuous evaluation as a feasible starting point for MSMEs